Recent Hepatitis E Virus Infection in Wild Boars and Other Ungulates in Japan - Virhuez-Mendoza, Milagros; Ishijima, Keita; Tatemoto, Kango; Kuroda, Yudai; Inoue, Yusuke; Nishino, Ayano; Yamamoto, Tsukasa; Uda, Akihiko; Hotta, Akitoyo; Kabeya, Hidenori; Shimoda, Hiroshi; Suzuki, Kazuo; et al. (Viruses, 2025)
Hepatitis E virus (HEV) is a zoonotic pathogen with multiple hosts, posing significant public health risks, especially in regions like Japan where game meat consumption is prevalent. This study investigated HEV infection and viral shedding in wild boars, sika deer, and Japanese serows across Japan. A total of 1896 serum samples were tested for anti-HEV antibodies, 1034 for HEV RNA, and 473 fecal samples for viral shedding. Anti-HEV antibodies were detected in wild boars from all seven prefectures studied, while HEV RNA was detected in wild boars from Fukuoka, Oita, and Miyazaki in southern Japan, as well as Yamaguchi prefecture. Genetic analysis revealed subtypes 3b, 4a, and 4g, with 3b being the most prevalent. Subtype 3b exhibited distinct geographical clustering, whereas 4g persisted exclusively in Yamaguchi for over 12 years. Infectious HEV particles were confirmed in wild boar feces, highlighting the risk of environmental contamination and zoonotic transmission. Sika deer showed no evidence of HEV infection, and only one Japanese serow tested positive for antibodies without detectable RNA. These findings underscore the importance of ongoing surveillance to assess the zoonotic risks from game meat consumption and prevention of HEV transmission to humans.